10. The Impact of the Verigene® Gram-positive Blood Culture Panel on the Management of Vancomycin Resistant enterococci Bloodstream Infections in a Multi-site Cohort Study. (31st December 2020) - Jackson, Christopher; Bandy, Sarah; Godinez, Will; Gawrys, Gerard; Lee, Grace
Abstract: Background: Vancomycin-resistant Enterococcus (VRE) bloodstream infections (BSIs) are associated with high morbidity and mortality. PCR-based rapid diagnostic tests provide prompt identification of infectious etiologies within hours. This study evaluated the impact of the Verigene® Gram-positive blood culture (GP-BC) panel on the outcomes on patients with VRE BSIs. Methods: A multi-center pre- and post-implementation retrospective cohort study was conducted at four large HCA Healthcare facilities. The implementation of Verigene® GP-BC and VigiLanz® surveillance software with real-time notifications to clinical pharmacists occurred in 2015. Adults > 18 years with VRE BSIs were evaluated over two time periods; pre-implementation (Pre; May 2011 - May 2013) and post-implementation (Post; May 2015 - May 2017). Patients were excluded if not admitted or were discharged/deceased before blood culture results. The primary outcome of this study was to compare time to optimal therapy (TOT). Secondary outcomes included hospital mortality, length of stay (LOS), and TOT comparing clinical pharmacy staffing models. Multivariable logistic regression models were used to identify independent predictors. Adjusted ORs (aOR) and their 95% CIs were reported. Results: A total of 104 patients with VRE BSIs were included in the study; 50 and 54 in the pre- and post-implementation periods, respectively. There were no differences in baseline characteristics between the groups. TOT was significantly shorter in the post vs. pre group (29 hrs ± 36 vs. 67 hrs ± 124, p=0.03 ). There was significantly lower hospital mortality when comparing the pre- and post-implementation periods (32% vs. 11%, p< 0.01 ). After adjusting for age, sex, severity of illness, treatment/dose, the post implementation period was independently associated with reduced hospital mortality (aOR 0.21, CI 0.61–0.73, p=0.01 ). There were no significant differences in LOS or clinical pharmacy staffing models on TOT. Baseline Characteristics Primary and secondary outcomes data Conclusion: The implementation of the Verigene® BC-GP with VigiLanz® substantially decreased TOT for VRE BSIs and was associated with reduced hospital mortality. This study highlights the positive impact of RDTs on shorter TOT and associated clinical outcomes. Disclosures: All Authors : No reported disclosures